Intense Exercise for Survival among Men with Metastatic Castrate-Resistant Prostate Cancer (INTERVAL-GAP4): a multicentre, randomised, controlled phase III study protocol. Issue 5 (14th May 2018) - Newton, Robert U; Kenfield, Stacey A; Hart, Nicolas H; Chan, June M; Courneya, Kerry S; Catto, James; Finn, Stephen P; Greenwood, Rosemary; Hughes, Daniel C; Mucci, Lorelei; Plymate, Stephen R; Praet, Stephan F E; et al.
Abstract : Introduction: Preliminary evidence supports the beneficial role of physical activity on prostate cancer outcomes. This phase III randomised controlled trial (RCT) is designed to determine if supervised high-intensity aerobic and resistance exercise increases overall survival (OS) in patients with metastatic castrate-resistant prostate cancer (mCRPC). Methods and analysis: Participants (n=866) must have histologically documented metastatic prostate cancer with evidence of progressive disease on androgen deprivation therapy (defined as mCRPC). Patients can be treatment-naïve for mCRPC or on first-line androgen receptor-targeted therapy for mCRPC (ie, abiraterone or enzalutamide) without evidence of progression at enrolment, and with no prior chemotherapy for mCRPC. Patients will receive psychosocial support and will be randomly assigned (1:1) to either supervised exercise (high-intensity aerobic and resistance training) or self-directed exercise (provision of guidelines), stratified by treatment status and site. Exercise prescriptions will be tailored to each participant's fitness and morbidities. The primary endpoint is OS. Secondary endpoints include time to disease progression, occurrence of a skeletal-related event or progression of pain, and degree of pain, opiate use, physical and emotional quality of life, and changes in metabolic biomarkers. An assessment of whether immune function, inflammation, dysregulation of insulin and energy metabolism, and androgen biomarkers are associated with OS will be performed, and whether they mediate the primary association between exercise and OS will also be investigated. This study will also establish a biobank for future biomarker discovery or validation. Ethics and dissemination: Validation of exercise as medicine and its mechanisms of action will create evidence to change clinical practice. Accordingly, outcomes of this RCT will be published in international, peer-reviewed journals, and presented at national and international conferences. Ethics approval was first obtained at Edith Cowan University (ID: 13236 NEWTON), with a further 10 investigator sites since receiving ethics approval, prior to activation. Trial registration number: NCT02730338 .